Cellular and Molecular Implications of Mature Adipocyte Dedifferentiation - Wei, Shengjuan (Ivyspring International Publisher, 2013)
There is a voluminous amount of scientific literature dealing with the involvement of adipocytes in molecular regulation of carcass composition, obesity, metabolic syndrome, or diabetes. To form adipocytes (process termed adipogenesis) nearly all scientific papers refer to the use of preadipocytes, adipofibroblasts, stromal vascular cells or adipogenic cell lines, and their differentiation to form lipid-assimilating cells containing storage triacylglyceride. However, mature adipocytes, themselves, possess ability to undergo dedifferentiation, form proliferative-competent progeny cells (the exact plasticity is unknown) and reinitiate formation of cells capable of lipid metabolism and storage. The progeny cells would make a viable (and alternative) cell system for the evaluation of cell ability to reestablish lipid assimilation, ability to differentially express genes (as compared to other adipogenic cells), and to form other types of cells (multi-lineage potential). Understanding the dedifferentiation process itself and/or dedifferentiated fat cells could contribute to our knowledge of normal growth processes, or to disease function. Indeed, the ability of progeny cells to form other cell types could turn-out to be important for processes of tissue reconstruction/engineering and may have implications in clinical, biochemical or molecular processes.